Społeczne uwarunkowania restrukturyzacji szpitali - Jasińska, Joanna (The effects of social conditions on the restructurisation of hospitals, 2005)
In this article we have indicated the problems of social conditions and their effects on hospital restructurisation. Hospitals are in effect a basic element in the health care system. At this level takes place the actual process of assimilating changes in the system and here arises a series of complications that causes difficulties in their institution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 587-593